German Central Asia policy after the "Zeitenwende": Challenges and opportunities for a strategic partnership - Manfred Huterer; Jacopo Maria Pepe; Andrea Schmitz (Stiftung Wissenschaft und Politik (SWP), 2024)
Russia's war against Ukraine and the geopolitical shifts on the Eurasian continent have brought Central Asia back into the focus of Germany and the EU. Germany's strategic regional partnership with Central Asia, which was announced last autumn, offers promising potential for cooperation. However, deepening sectoral cooperation is associated with challenges that require a realistic assessment of the individual areas of engagement. Precise context analyses are essential to avoid misperceptions and false expectations. Germany's involvement should be long-term and primarily aim to strengthen the crisis resilience of the Central Asian countries. A key prerequisite for this is support for intra-regional cooperation, particularly in logistics, electricity infrastructure and water management.r more pragmatism in climate diplomacy and policy instruments. Moreover, to keep pace with competitors, policymakers should adopt a proactive approach to CCS vis-à-vis technology and industry.
Keywords: 320; Central Asia; Strategic Partnership; Kazakhstan; Kyrgyzstan; Tajikistan; Turkmenistan; Uzbekistan